Mathematisch fundiertes fachdidaktisches Wissen (mathematica didactica, 2021)
This paper intends to contribute to discussions centering on a number of questions: Which aspects constitute knowledge on didactics of mathematics? Which relationdoes knowledge on didactics of mathematics bear to the science of mathematics? Which qualifications are being required to develop and mediate knowledge on didactics of mathematics in a mathematically substantiated manner?